Comparison of the effectiveness of melamine derived graphitic carbon nitrides based photocatalysts towards the degradation of Rhodamine B. (2022) - Sakthivel, C.; Marappan, M.; Sankara Narayanan, T.S.N.
Abstract: Graphitic carbon nitride (GCN) is a well-known visible light photocatalyst. Bulk GCNs derived from various types of precursors often exhibit lower photocatalytic efficiencies towards degradation of organic pollutants due to their lower surface area and porosity. Exfoliation, formation of mesoporous structure, development of heterojunctions, doping with metals and non-metals, and intercalation are some of the strategies adopted to improve the efficiency of GCN. Melamine is the most commonly used precursor for the synthesis of GCN. However, the bulk GCN derived from melamine exhibits poor photocatalytic activity, warranting improvement. Mixing of melamine with ammonium based salts is considered as a useful approach to prepare GCN nanosheets with a higher surface area and porosity. The present study aims to compare the effectiveness of GCNs derived from melamine (MGCN) as well using a mixture of melamine and ammonium nitrate (ANGCN), melamine and ammonium carbonate (ACGCN) and, melamine and ammonium chloride (AGCN) in 1:4 ratios under visible light irradiation using Rhodamine B as a model pollutant. The study reveals that ANGCN, ACGCN and AGCN exhibit much better degradation efficiency than MGCN. The GCNs can be ranked as AGCN > ACGCN > ANGCN > MGCN in terms of their efficiency towards the degradation of Rhodamine B. The difference in efficacy among them is mainly due to the extent of the exfoliation of catalyst, development of nanosheets and porosity, which is relatively higher for AGCN, ANGCN and ACGCN. The study concludes that mixing melamine with NH4 Cl/NH4 CO3 /NH4 NO3 at 1:4 ratios enables the formation of GCNs with desired characteristics and among them those prepared using NH4 Cl (AGCN) is promising due to its higher porosity, development of more number of nanosheets, more negative Zeta potential and lower rate of recombination of charge carriers.